Ge-stell and the Specters of the Spectrum - Erik Eppel (Forum, 2008)
No more than a few hundred meters separate the site where Gugliemo Marconi first witnessed the extraordinary effects of Hertzian waves in 1895, and the site where armored vehicles crashed through barricades in order to put down a riot allegedly incited by local radio station, Radio Alice, in 1977. When considering that the former represents the point of departure for one of the most important inventions of the 20th century and the latter represents one of its most paradigmatic instantiations, we might question whether their proximity is something other than coincidental. Affirming that this is more than a coincidence, however, carries with it the necessity and responsibility to demonstrate some causal relationship between Marconi's invention and its appropriation, circa 80 years later, by a group of students and activists in search of means to communicate, organize, experiment and play.